Numerical simulation of evolution patterns in temperature fields during the frozen excavation and underwater pouring of garage shafts - Jiajun Ji; Tingting Luo; Chenyi Zhang; Tao Han; Yu Zhang; Haipeng Li; Xiaodong Zhao; Guangsi Zhao; Yang Zhou; B.N. Madhusudhan; Zhijiang Yang; Weihao Yang (Cold Regions Science and Technology, 2026)

Radial built-in electric field engineering in type-II p–n Janus tubular nanofibers for room-temperature NO2 sensing - Zeju Zhang; Yutong Zou; Xiaowei Li; Yu Liu; Wanying Cheng; Haipeng Dong; Liwei Zhang; Ruyi Liu; Hongwei Gao; Xinghua Li; Changlu Shao; Yichun Liu (Chemical Engineering Journal, 2026)

Mapping mollic epipedon thickness via ground-penetrating radar based on the combined method of Variational Mode Decomposition and Average Envelope Amplitude - Haipeng Lu; Xiangming Zhu; Wenjuan Zheng; Bin Zhang; Tianhao Wang; Yu Zhang; Meiling Fu; Enhua Ran (Soil and Tillage Research, 2026)

A multifunctional bioinspired superhydrophobic sponge with photothermal conversion and flame retardancy for integrated oil-water separation and viscous oil remediation - Junli Yu; Jihong Fu; Qichao Wu; Mengdie Li; Boshen Wang; Haipeng Zhang; Ronglan Wu (Journal of Hazardous Materials, 2026)

Thermal pumping of the Tibetan Plateau Summer Monsoon and its association with the South Asian High and East Asian summer monsoon variability - Lizi Wang; Zeyong Hu; Haipeng Yu; Ya Hou; Jinyu Zhang; Xiangyuan Lou; Guantian Wang (Atmospheric Research, 2026)

Synergistic effects of hydrochar and arbuscular mycorrhizal fungi on zinc uptake in maize: Roles of mycelial networks and rhizosphere processes - Haipeng Xu; Yuqing Liu; Xiao Zhang; Hongyu Si; Hewei Yu; Yumin Liu; Bing Wang; Xiuxiu Chen (Plant and Soil, 2026)

Dominant role of circulation induced “Warm Arctic-Cold Eurasia” pattern in the record-breaking cold event over Central Eurasia in December 2023 - Ruixia Guo; Haipeng Yu; Zeyong Hu; Kangjie Ma (Climate Dynamics, 2026)

Local Evapotranspiration and Atlantic Decadal Variability Dominate the Humidification of Northwest China - Haipeng Yu; Yongqi Gong; Jianping Huang; Qiang Zhang; Yu Ren; Hongyu Luo; Xin Wang; Shanling Cheng; Jie Zhou (Advances in Atmospheric Sciences, 2026)

Super retarding-flame wood - Sen Gao; Jing Ren; Baoping Zhang; Lixian Yang; Yiqiang Wu; Yingying Zhang; Leitao Cao; Qing Li; Chunlei Zhang; Mingyue Miao; Haipeng Yu; Shouxin Liu; et al. (Science Bulletin, 2026)

Operational threshold and associated mechanisms in composting remediation of diesel-contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Environmental Management, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Redox-active co-pyrolytic carbon enhances electron transfer and mitigates petroleum hydrocarbon hazards in contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Hazardous Materials, 2026)

Removal potential and mechanism of doxycycline hydrochloride by Fe/Ca-loaded biochar synthesized by one-step pyrolysis - Jiamin Yi; Tiantian Yue; Haipeng Zhang; Xue Han; Liheng Liu; Guo Yu; Xuehong Zhang (Journal of Environmental Chemical Engineering, 2026)

The influence of precipitation recycling processes on summer precipitation variability over Northwest China - Yongli He; Zhen Tang; Chutao Lan; Boyuan Zhang; Jingjing Jia; Haipeng Yu (Climate Dynamics, 2026)

Effects of New-Type Fertilizers on Dry Matter Accumulation, Yield and Quality of Wheat in the Shajiang Black Soil Region of Northern Anhui - Lijuan Zhou; Wenjing Ding; Han Zheng; Hao Cheng; Yuanyuan Chen; Yongbo Yu; Zhaoliang He; Zhenglai Huang; Haipeng Zhang (International Journal of Plant Production, 2026)

Unveiling microplastics contamination in ice cream via μ-FTIR analysis: The invisible crisis of frozen desserts - Haipeng Zhang; Jun Tang; Jihong Fu; Boshen Wang; Junli Yu; Xakura Xarpby; Xinyue Li (Journal of Environmental Chemical Engineering, 2026)

Inhibition mechanism of sodium bicarbonate on micron-sized aluminum dust explosions: Computational fluid dynamics modeling and experimental validation - Jing Luo; Wei Gao; Tianjiao Zhang; Kai Zhang; Songling Jin; Yu Hong; Haipeng Jiang (Chemical Engineering Journal, 2026)

Preoptic Neural Circuitry for Dramatic and Gentle Thermoregulation - Ruiqi Pang; Haipeng Yu; Jincheng Wang; Zhiyue Shi; Huizhong Wen; Guangyan Wu; Xuan Zhang; Yueting Zhang; Qiaoqian Wei; Bo Li; Xueqing Yi; Kai Liu; et al. (Neuroscience Bulletin, 2026)

Enhancing methane emission assessment for urban gas distribution pipelines: Model modification and field validation - Zhengyi Xie; Jianfeng Tang; Yu Zhao; Haipeng Zhu; Xuanke Li; Yuchen Niu (Process Safety and Environmental Protection, 2026)

Machine learning-assisted oxide semiconductor sensor array for accurate discrimination of alcohol gases - Tong Liu; Yu Liu; Xiaowei Li; Dongxiao Lu; Haipeng Dong; Zeju Zhang; Xinghua Li; Changlu Shao; Yichun Liu (Chemical Engineering Journal, 2026)

Creep behaviors of artificial freezing columnar ice prepared in successive high-pressure state - Chenyi Zhang; Tingting Luo; Tao Han; Haipeng Li; B.N. Madhusudhan; Jiajun Ji; Yu Zhang; Weihao Yang (Cold Regions Science and Technology, 2026)

Dynamic oil fume exhaust method and calculation formula suitable for residential kitchens in cold regions - Kailiang Huang; Run Bai; Guohui Feng; Xiaoxu Li; Chaoying Fan; Helu Cao; Haipeng Yu (Building and Environment, 2026)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Effects of diets on survival, growth, and feed efficiency in early juvenile sea urchins Salmacis sphaeroides and Heliocidaris crassispina - Lei You; Dong Wang; Weihuan Yu; Zhenhao Lin; Xuanliang Wang; Haipeng Qin; Xianpei Huang; Zonghe Yu (Aquaculture International, 2025)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Impact of summer atmospheric heat source over the Tibetan Plateau on the interannual variability of precipitation in Northwest China - Hongyu Luo; Haipeng Yu; Zeyong Hu; Jie Zhou; Shanling Cheng; Yu Ren; Haojie Wu; Yongqi Gong (Climate Dynamics, 2025)

Early dry season changed the abundance and composition of soil antibiotic resistance genes in Dongting Lake wetland, China - Guxiang Xu; Yu Lou; Haipeng Wu; Juan Dai; Kenan Tian; Lean Zhou; Wenhao Li; Zeren Wang (Journal of Environmental Chemical Engineering, 2025)

Enhancement of high-solid chicken manure anaerobic digestion: Insights into ammonia air stripping pretreatment for microbial resilience and hydraulic retention stabilization - Xinhui Yu; Fangtong Wei; Haipeng Wang; Shaojie Bi; Changjiang Zhao; Yanjie Wang (Biomass and Bioenergy, 2025)

WSSV Infection in the Gut Microbiota of the Black Tiger Shrimp Penaeus monodon - Youhong Wang; Xiaolu Wang; Chunlei Gai; Yuanyuan Li; La Xu; Shuxian Wang; Li Li; Xiaoqing Yu; Ranghui Fu; Jing Diao; Haibin Ye; Ying Fan; et al. (Fishes, 2025)
This study investigated the impacts of white spot syndrome virus (WSSV) on the gut microbiota of Penaeus monodon through a comparative microbiota analysis of infected and healthy shrimp using 16S rDNA sequencing. The WSSV-infected shrimp exhibited characteristic white spots, reduced feeding activity, and behavioral lethargy preceding 100% mortality. The comparative microbiota analysis revealed a significantly diminished α-diversity in the infected specimens, marked by phylum-level dominance shifts from Proteobacteria (72.68%) and Firmicutes (11.27%) in the controls to Cyanobacteria (75.51%) and Proteobacteria (15.63%) in the WSSV-infected shrimp. An LEfSe analysis identified Arthrospira_PCC-7345 and Halochromatium as significantly enriched taxa during infection, contrasting with depleted populations of Ruegeria, Marivita, Bacillus, and seven other genera. The distinct dysbiosis pattern characterized by the pathogen-favored taxa proliferation and commensal species suppression demonstrates WSSV-associated microbiota restructuring, potentially contributing to disease progression in farmed P. monodon. These findings establish intestinal microbial biomarkers for early WSSV detection in aquaculture systems.

Bacterial membrane-coated bacteriform manganese dioxide platforms amplify phototherapeutic efficacy through the cGAS-STING pathway - Shining Niu; Qian Chen; Lulu Yu; Xiao Wang; Haipeng Yu; Mei Wen; Zhigang Chen; Nuo Yu; Kun Li (Chemical Engineering Journal, 2025)

Isolation, Identification, and Virulence Properties of Enterobacter bugandensis Pathogen from Big-Belly Seahorse Hippocampus abdominalis - Haibin Ye; Chenhao Teng; Yueqi Yang; Yiyao Liu; Li Li; Ying Fan; Youhong Wang; Jing Diao; Lingling Yu; Chunlei Gai; Haipeng Cao (Fishes, 2025)
Nowadays, members of the genus Enterobacter have been documented as human and aquaculture pathogens. To date, no reports have described Enterobacter bugandensis infecting Hippocampus abdominalis. In the present study, an isolate of E. bugandensis, designated H4, was identified as a causative pathogen in cultured H. abdominalis following Koch’s postulate, and its virulence properties were further described. The isolate’s genome consisted of a single circular chromosome and harbored several virulence and resistance genes, including, but not limited to, csgG, acrB, hcp, gndA, galF, rpoS, fur, rcsB, and phoP involved in adherence, antimicrobial activity, effector delivery systems, immune modulation, and regulation, as well as baeR, blaACT-49, ramA, hns, ftsI, acrA, gyrA, fabI, crp, oqxB, parE, gyrB, phoP, rpoB, tuf, ptsI, and fosA2 functioning against aminoglycoside, cephamycin, disinfecting agent and antiseptic, fluoroquinolone, macrolide, peptide, and other antimicrobials. Additionally, the isolate exhibited multiple resistance to cephalosporins, penicillins, and tetracyclines and demonstrated a median lethal dose (LD50) of 4.47 × 105 CFU/mL in H. abdominalis. To our knowledge, this is the first study to describe E. bugandensis infecting H. abdominalis. These findings highlight the zoonotic potential of E. bugandensis and underscore the need for targeted health management in seahorse farming.

Land-atmosphere coupling characteristics in summer based on microwave radiometer data at Nagqu site of Tibetan Plateau - Guantian Wang; Zeyong Hu; Haipeng Yu; Genhou Sun; Ruijia Niu; Xin Wang (Atmospheric Research, 2025)

Unveiling the Hidden Impact: Hematoma Volumes Unravel Circuit Disruptions in Intracerebral Hemorrhage - Yingqing Wu; Qin Deng; Ranran Wei; Sen Chen; Fusheng Ding; Haipeng Yu; Ning Hu; Shilei Hao; Bochu Wang (Translational Stroke Research, 2025)

Advances in Research on Climate Change and Its Effects on the Arid and Semi-Arid Regions of China over the Past Century - Qiang Zhang; Jianping Huang; Jinhu Yang; Xiaodan Guan; Haipeng Yu; Biao Zhu; Hongli Zhang; Dongliang Han; Xinyang Yan; Guolong Zhang; Zesu Yang; Jian Zeng (Journal of Meteorological Research, 2025)

Sensitive amperometric immunosensor for pathogen antigen based on MoS2@AuNPs assembling dual-peptide as bioprobes with significant dual signal amplification - Zongmei Zheng; Mingyang Wang; Jinlong Yuan; Junchong Liu; Haipeng Yu; Zhonghuang Yang; Wanjian Liu; Aihua Liu (Analytica Chimica Acta, 2025)

Abrupt loss of species richness caused by ecosystem transition - Li Fu; Jianping Huang; Guolong Zhang; Dongliang Han; Lei Ding; Yun Wei; Xiaoyue Liu; Changyu Li; Haipeng Yu (Science Bulletin, 2025)

Multiple stimuli-responsive circularly polarized luminescent bio-composite films by coassembling cellulose nanocrystals and curcumin - Shaoyi Cao; Jingpeng Wang; Wenye Sun; Bang An; Mingcong Xu; Sha Luo; Chunhui Ma; Haipeng Yu; Zhijun Chen; Jian Li; Wei Li; Shouxin Liu (Carbohydrate Polymers, 2025)

Evaluation of hourly summer precipitation products over the Tibetan Plateau: A comparative analysis of IMERG, CMORPH, and TPHiPr - Jingjing Jia; Yongli He; Boyuan Zhang; Zixin Huo; Zhen Tang; Shanshan Wang; Haipeng Yu; Xiaodan Guan (Atmospheric Research, 2025)

Accelerated drying trends over Northeast Asia by anthropogenic forcing during 1948–2010 - Ruixia Guo; Jianping Huang; Haipeng Yu; Zeyong Hu (Atmospheric Research, 2025)

In-Situ formed Quasi-Homogeneous iontronic sensors with Ultrawide sensing range for Human-Machine interaction - Ao Yin; Ruiguang Chen; Jin Ning; Jingjing Luo; Zhongqi Ren; Haipeng Liu; Yuan Meng; Peike Wang; Shuheng Fan; Xue Qi; Hailin Wang; Zherong Yu; et al. (Chemical Engineering Journal, 2025)

Impact of mid-high latitude circulation and surface thermal forcing on drought events in Central Asia - Yu Ren; Haipeng Yu; Jianping Huang; Jie Zhou; Hongyu Luo; Shanling Cheng (Climate Dynamics, 2025)

Tibetan Plateau Vortex Activity and Its Relationship With the Tibetan Plateau Summer Monsoon and Precipitation - Guantian Wang; Zeyong Hu; Haipeng Yu; Genhou Sun; Weiwei Fan; Ruijia Niu; Bofei Zhang (International Journal of Climatology, 2025)
The unique topography and location of the Tibetan Plateau (TP) often result in extreme weather events, which have led to disastrous consequences for the TP and its downstream regions. The TP summer monsoon (TPSM) and the TP vortex (TPV) play key roles in the transfer and redistribution of water vapour during the summer months on the TP and are increasingly active in summer and disappear in winter. However, it remains uncertain if a relationship between these systems. Understanding the relationship between these two systems is crucial for uncovering precipitation patterns on the TP, improving weather forecasting accuracy and reducing socioeconomic losses resulting from weather‐related disasters. On the basis of GLDAS and ERA5 reanalysis data from 1996 to 2022, the relationships between TPVs and the TPSM were explored in terms of their intensity and spatial characteristics, and their impacts on the spatial distributions of precipitation across the TP were examined in this study. The results indicated that the monthly mean TPSM index agreed very well with the TPV in terms of the annual number formed, duration and intensity, especially in July and August. The investigation of the movement of the center of the TPSM from May to October revealed that the center of the TPSM moves westward when the TPV is active and moves eastward when the TPV is less active. In years with a strong TPSM, the precipitation location generated by TPVs was biased toward the east. This finding could be attributed to the greater number of TPV events and the fact that the TPVs in years with a stronger TPSM moved eastward across a greater distance than those in years with a weaker TPSM. These findings highlightthe contribution of the joint relationship between the TPSM and TPV to seasonal circulation changes and could provide a new perspective for the study and prediction of precipitation distributions on the TP.

Does a not-for-profit minority institutional shareholder promote corporate green innovation? A quasi-Natural experiment - Haipeng Yu; Xiaoke Cheng; Qian Sun (Journal of Environmental Management, 2025)

A Machine Learning-Based Observational Constraint Correction Method for Seasonal Precipitation Prediction - Bofei Zhang; Haipeng Yu; Zeyong Hu; Ping Yue; Zunye Tang; Hongyu Luo; Guantian Wang; Shanling Cheng (Advances in Atmospheric Sciences, 2025)

Methane emissions at pressure-regulating stations in China: A comparative analysis of various quantitative methods - Zhengyi Xie; Jianfeng Tang; Haipeng Zhu; Fei Li; Yu Zhao; Xuanke Li; Tong Li (Science of The Total Environment, 2024)

Spherical radial basis functions model: approximating an integral functional of an isotropic Gaussian random field - Guobin Chang; Xun Zhang; Haipeng Yu (Journal of Geodesy, 2024)

Process exploration of domestication, start-up and rapid recovery strategies for anaerobic digestion of sole corn stover: Methane production efficiency and dominant microbial responses - Haipeng Wang; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Cleaner Production, 2024)

Genomic selection for agronomical phenotypes using genome-wide SNPs and SVs in pearl millet - Haidong Yan; Yarong Jin; Haipeng Yu; Chengran Wang; Bingchao Wu; Chris Stephen Jones; Xiaoshan Wang; Zheni Xie; Linkai Huang (Theoretical and Applied Genetics, 2024)

Estimation of peak wave period from surface texture motion in videos - Haipeng Yu; Xiaoliang Chu; Guang Yuan (Acta Oceanologica Sinica, 2024)

Promotion of lignin depolymerization and cellulose utilization via the coupling effects of DDQ pre-oxidation and HCOOH extraction - Jiamin Ye; Haipeng Yu; Zhiwen Jia; Wanyu Li; Linghao Li; Hong Wang; Enchen Jiang; Yan Sun; Xiwei Xu (Chemical Engineering Journal, 2024)

Accumulated charge density at the interface boosts the urea oxidation reaction activity of Ni3N/Ni3S2 heterointerface - Haipeng Liu; Peike Wang; Xue Qi; Ao Yin; Yuxin Wang; Yang Ye; Jingjing Luo; Zhongqi Ren; Suzhu Yu; Jun Wei (Chemical Engineering Journal, 2024)

The full utilization of bagasse via deep eutectic solvent pretreatment for low-condensed lignin and cellulose smart indicator film - Wanyu Li; Jiamin Ye; Zhiwen Jia; Haipeng Yu; Linghao Li; Hong Wang; Enchen Jiang; Yan Sun; Xiwei Xu (Chemical Engineering Journal, 2024)

Remote Effects of double Typhoons on Record-breaking Rainfall: A case Study in North China - Jie Zhou; Haipeng Yu; Yu Ren; Yaoxian Yang; Xiaoyue Liu; Guanghua Chen; Zhanhong Ma; Wen Zhao; Siyu Chen; Yun Wei; Chenxi Liu; Jinxia Zhang (Atmospheric Research, 2024)

Modeling the transport of PM10, PM2.5, and O3 from South Asia to the Tibetan Plateau - Yuling Hu; Haipeng Yu; Shichang Kang; Junhua Yang; Xintong Chen; Xiufeng Yin; Pengfei Chen (Atmospheric Research, 2024)

Flood risk transfer analysis based on the “Source-Sink” theory and its impact on ecological environment: A case study of the Poyang Lake Basin, China - Zhizhou Zhu; Shuliang Zhang; Yaru Zhang; Haipeng Lu; Xinghua Feng; Hengxu Jin; Yu Gao (Science of The Total Environment, 2024)

Low-carbon environment-friendly economic optimal scheduling of multi-energy microgrid with integrated demand response considering waste heat utilization - Haipeng Chen; Shuoshi Yang; Jindong Chen; Xingyu Wang; Yang Li; Siyuan Shui; Hao Yu (Journal of Cleaner Production, 2024)

Decadal modulation of temperature pattern over East Asia by Pacific Decadal Oscillation - Ruixia Guo; Jianping Huang; Haipeng Yu; Huizhen Zhao; Zeyong Hu (Atmospheric Research, 2024)

Nepenthes alata inspired anti-sticking surface via nanosecond laser fabrication - Guang Liu; Jiajun Yang; Kaiteng Zhang; Haipeng Yan; Yu Yan; Yingdong Zheng; Liwen Zhang; Zehui Zhao; Lixin Wang; Guang Yang; Huawei Chen (Chemical Engineering Journal, 2024)

Glycosidic bond protection of cellulose during solvent dissolution by coordination interaction competition strategy - Zhihan Tong; Suqing Zeng; Xiaona Li; Wen Wang; Qinqin Xia; Haipeng Yu (Carbohydrate Polymers, 2024)

Biochar from phytoremediation plant residues: a review of its characteristics and potential applications - Xueyan Fan; Chunyan Du; Lu Zhou; Yi Fang; Guanhao Zhang; Honghao Zou; Guanlong Yu; Haipeng Wu (Environmental Science and Pollution Research, 2024)

Electron transfer and microbial mechanism of synergistic degradation of lignocellulose by hydrochar and aerobic fermentation - Chengze Yu; Mingxiao Li; Haipeng Huang; Jie Yan; Xiaolei Zhang; Tao Luo; Meiying Ye; Fanhua Meng; Tiecheng Sun; Jiaqi Hou; Beidou Xi (Bioresource Technology, 2024)

Insights into the nitrogen transformation mechanism of Pseudomonas sp. Y15 capable of heterotrophic nitrification and aerobic denitrification - Jinliang Chen; Liang Shen; Yu Li; Haipeng Cao; Cuixue Chen; Guoliang Zhang; Zehai Xu; Yinghua Lu (Environmental Research, 2024)

Extreme heat event over Northwest China driven by Silk Road Pattern teleconnection and its possible mechanism - Jie Zhou; Haipeng Yu; Peiqiang Xu; Wen Zhao; Bofei Zhang; Yu Ren; Shanling Cheng; Yongqi Gong; Yaoxian Yang (Atmospheric Research, 2024)

Responses of soil microbial communities to manure and biochar in wheat cultivation of a rice-wheat rotation agroecosystem in East China - Jun MENG; Wenjin LI; Yingbo QIU; Zhangtao LI; Linze LI; Yu LUO; Haipeng GUO; Yijun YU; Shengdao SHAN; Huaihai CHEN (Pedosphere, 2023)

Impact of the Shrinkage of Arctic Sea Ice on Eurasian Snow Cover Changes in 1979–2021 - Qian Yang; Shichang Kang; Haipeng Yu; Yaoxian Yang (Advances in Atmospheric Sciences, 2023)

Novel supramolecular deep eutectic solvent pretreatment for obtaining fluorescent lignin and promoting biomass pyrolytic saccharification - Zhiwen Jia; Shiyang Wang; Haipeng Yu; Wanyu Li; Jiamin Ye; Yihao Hu; Cong Liu; Zijian Ye; Yan Sun; Xiwei Xu (Bioresource Technology, 2023)

Evaluating the potential of achieving carbon neutrality at the neighborhood scale in urban areas - Haipeng Ye; Yu Li; Donghui Shi; Dan Meng; Ninghui Zhang; Hongrui Zhao (Sustainable Cities and Society, 2023)

Toward understanding Fischer − Tropsch synthesis on cobalt carbides from first principles and microkinetic analysis - Haipeng Yu; Lingtao Wang; Yingzhe Yu; Guochao Yang; Minhua Zhang (Chemical Engineering Journal, 2023)

Provenance and tectonic setting of the Yimianpo Group in the southeastern Songnen–Zhangguangcai Range Block: constraints on the closure of the Mudanjiang Ocean - Mishan Zhong; Jin Liu; Zhenghong Liu; Jundian Chen; Hongchao Yu; Haipeng Wang; Junshi Lu; Zijie Wu; Mingchen Pan; Qi Wang; Yilong Wang (Geosciences Journal, 2023)

An approach for upgrading behavior and bio-oil production using CO2-assisted cellulose pyrolysis in cobalt-based Ce/Fe/Mg composite catalyst - Haipeng Liu; Haifeng Jiang; Jiaxing Song; Ling Zhang; Yu Zhang; Yuhang Li; Wenpeng Hong (Fuel, 2023)

Biopanning of specific peptide for SARS-CoV-2 nucleocapsid protein and enzyme-linked immunosorbent assay-based antigen assay - Pengxin Ma; Junchong Liu; Shuang Pang; Wenhao Zhou; Haipeng Yu; Mingyang Wang; Tao Dong; Yanbo Wang; Qiqin Wang; Aihua Liu (Analytica Chimica Acta, 2023)

Synergistic inhibition of thermal runaway propagation of lithium-ion batteries by porous materials and water mist - Yu Zhu; Yuxin Zhou; Haipeng Gao; Zhirong Wang; Wei Bai; Dongxu Ouyang; Junling Wang (Journal of Cleaner Production, 2023)

Impact of the leading atmospheric wave train over Eurasia on the climate variability over the Tibetan Plateau during early spring - Yaoxian Yang; Yimin Liu; Zeyong Hu; Haipeng Yu; Jinxiao Li; Yongkun Xie; Qian Yang (Climate Dynamics, 2023)

Simulated impacts of the wetter arid area of Northwestern China on the energy budget and atmospheric circulation over Tibetan Plateau and central part of North China plain in summer - Di Ma; Xianhong Meng; Shihua Lv; Yaohui Li; Haipeng Yu; Lele Shu; Lin Zhao; Zhaoguo Li (Atmospheric Research, 2023)

‘Asian water towers’ are not a sustainable solution to the downstream water crisis - Xuejing Leng; Xiaoming Feng; Bojie Fu; Qidong Shi; Haipeng Ye; Yu Zhang (Science of The Total Environment, 2023)

Highly flexible all-inorganic nanofiber networks with stress-accommodating microstructure for light-activated wearable chemiresistive sensor - Xiaowei Li; Yujing Tang; Wanying Cheng; Yu Liu; Haipeng Dong; Xinghua Li; Changlu Shao; Shencheng Fu; Yichun Liu (Chemical Engineering Journal, 2023)

Effects of CO2 injection volume and formation of in-situ new phase on oil phase behavior during CO2 injection for enhanced oil recovery (EOR) in tight oil reservoirs - Mingsheng Zuo; Hao Chen; Xinyu Qi; Xiliang Liu; Chenghao Xu; Haizeng Yu; Mahaman Sidi Brahim; Yi Wu; Haipeng Liu (Chemical Engineering Journal, 2023)

Future evolution of global land surface air temperature trend based on Coupled Model Intercomparison Project Phase 6 models - Wen Wu; Fei Ji; Shujuan Hu; Yongli He; Yun Wei; Zhenhao Xu; Haipeng Yu (International Journal of Climatology, 2022)
In recent decades, global warming has been an indisputable fact. The increase in extreme events accompanied by the rise in temperature has huge influences on many aspects of the society and economy globally. As a result, forecasting how global temperatures will change and evolve in the future is crucial, but it is restricted by the accuracy and uncertainty of model simulations. Based on ensemble empirical mode decomposition (EEMD) method, this study first evaluates the performance of the CMIP6 models in simulating different timescale components including high‐frequency components (HFC), low‐frequency components (LFC), and secular trend (ST) of surface air temperature (SAT). The results show that the performance of the CMIP6 models in simulating the ST is better. Following the observation constraint method's correction of CMIP6 model simulations, we investigate the evolution characteristics of future temperature secular trends under different Shared Socioeconomic Pathway (SSP) scenarios. The results show that under SSP245 scenario, the rise of SAT first appeared in northwest and east North America and eastern Europe. The spatial distribution of evolution characteristic under the SSP585 scenario is similar to that of the SSP245 scenario but with a larger magnitude. However, more pronounced differences appear in warming rate, which shows a downward trend over time under the SSP245 scenario and an upward trend with time under the SSP585 scenario.

A New Dual-peak Fluorescent Probe for Water Content Detection Made From Taxus - Gang Wang; Yaping Li; Haipeng Chen; Shuqin Tang; Yiyang Cheng; Yuhong Yu; Abdul Qayoom Majeedano; Shangrao Pu; Gang Wang (Journal of Fluorescence, 2022)

Abscisic acid synthesis and root water uptake contribute to exogenous methyl jasmonate-induced improved tomato drought resistance - Jiakun Yan; Haipeng Li; Yu Li; Nan Zhang; Suiqi Zhang (Plant Biotechnology Reports, 2022)

Brittleness evaluation method of shale based on confining pressure correction - Lifeng Liu; Meng Guan; Haitao Zhao; Haipeng Wang; Tianyu Gao; Yu Jiang (Acta Geophysica, 2022)

Bias‐corrections on aridity index simulations of climate models by observational constraints - Haipeng Yu; Qiang Zhang; Yun Wei; Chenxi Liu; Yu Ren; Ping Yue; Jie Zhou (International Journal of Climatology, 2022)
Aridity Index (AI) indicates the balance between water supply and water demand on the atmosphere–land interface. Despite continuous improvements, coupled climate models still have significant systematic errors in simulating AI in terms of temporal and spatial variabilities. One of the approaches to bias‐correct simulations is extracting the linear relationship between historical observations and model outputs by utilizing the empirical orthogonal function (EOF). In this study, the methodology of ensemble EOF‐based bias‐correction by observational constraints is developed based on previous bias‐correction approach, with the improvement on seeking the optimal combinations of the leading modes with sensitivity test and replacing the certain correction with the ensemble means of optimal members. In verification, the ensemble mean of Coupled Model Intercomparison Project phase 5 (CMIP5‐EM) is bias‐corrected towards the CPC/GLDAS observations, and the extracted leading modes present high correlations with internal climate variability. By cross‐validation and posteriori independent validation of hindcasts over the historical period (1948–2005), the ensemble EOF‐based bias‐correction could better present spatial patterns compared to the CMIP5‐EM after systematic bias‐correction, as indicated by the anomaly correlation and the root mean square error. The verifications also indicate that the temporal variability in aridity over different dryland regions is much closer to that in the observations and that the dryland subtype changes are improved significantly by bias‐corrections. Besides, another observational dataset of UDel/CRU is applied to assess the uncertainty on different datasets and the improvement on skill scores is robust. The above results verify that the ensemble EOF‐based bias‐corrections provide better reference for assessing and projecting global aridity changes by climate models.

A 17 ka multi‐proxy paleoclimatic record on the northeastern Tibetan Plateau: implications for the northernmost boundary of the Asian summer monsoon during the Holocene - Haipeng Wang; Yu Hu; Xu Zhang; Feiya Lv; Xueyang Ma; Duo Wu; Fahu Chen; Aifeng Zhou; Juzhi Hou; Jianhui Chen (International Journal of Climatology, 2022)
Knowledge of the paleoclimatic record of the northeastern Tibetan Plateau (NETP) can potentially improve our understanding of the evolution of the Asian summer monsoon (ASM). However, the history of climate change and inferred spatial extent of the ASM on the NETP since the last deglaciation remain unclear. Here, we use several environmental proxies from the sediments of Hala Lake (beyond the modern limit of ASM), including chironomids, loss‐on‐ignition, grain size and element data, to explore the climatic history of the NETP and the northern boundary of the ASM since the last deglaciation. The results document a series of climatic events during the deglaciation, including Heinrich Event 1, the Bølling–Allerød interstadial and the Younger Dryas event. The records also reveal the timing of the megathermal and precipitation maximum, the lake‐level maximum, and strongest chemical weathering, which occurred during ~10–7 ka. The inferred precipitation maximum during the early Holocene in the Hala Lake basin, which can be verified by the simulated precipitation change, is consistent with that in typical Indian summer monsoon (ISM) regions, suggesting that the ISM has penetrated into Hala Lake basin at that time. The monsoon‐dominated climate in the Hala Lake basin during the early Holocene and the westerlies‐dominated climate in the arid central Asia indicate that the maximum areal extent of the ASM on the NETP since the last deglaciation lay to the northwest of Hala Lake basin. In combination with other published records, the northernmost boundary of the ASM over China since the last deglaciation has been tentatively delineated, to shed some lights on this long‐standing debate.

Reduced graphene oxide modified Z-scheme AgI/Bi2MoO6 heterojunctions with boosted photocatalytic activity for water treatment originated from the efficient charge pairs partition and migration - Chunyan Du; Lu Yang; Shiyang Tan; Jiahao Song; Zhuo Zhang; Shitao Wang; Ying Xiong; Guanlong Yu; Hong Chen; Lu Zhou; Haipeng Wu; Yuanyuan Liu (Environmental Science and Pollution Research, 2021)

Changes of Extreme Precipitation and its Associated Mechanisms in Northwest China - Shan Lu; Zeyong Hu; Haipeng Yu; Weiwei Fan; Chunwei Fu; Di Wu (Advances in Atmospheric Sciences, 2021)

Downward continuation of airborne gravity data based on iterative methods - Haipeng Yu; Guobin Chang; Nijia Qian; Shubi Zhang; Wenyuan Zhang (Acta Geodaetica et Geophysica, 2021)

Improving China’s summer precipitation prediction in 2020 by observational constrained bias correction - Yun Wei; Haipeng Yu; Jianping Huang; Xiaoyue Liu; Jie Zhou (Theoretical and Applied Climatology, 2021)

Characterization and complete genome analysis of Bacillus velezensis CB6 revealed ATP synthase subunit α against foodborne pathogens - Haipeng Zhang; Guan-yi Xu; Changsi Mao; Yuxuan Xu; Wenlong Dong; Muhammad Inam; Siyu Pan; Renge Hu; Yiming Wang; Yu Wang; Hongxia Ma; Lingcong Kong (Archives of Microbiology, 2021)

Reduction in extreme climate events and potential impacts by the use of technological advances - Ting Wei; Changxin Liu; Wenjie Dong; Haipeng Yu; Shili Yang; Qing Yan; Zhixin Hao (International Journal of Climatology, 2021)
Technological advances have the potential to balance climate change mitigation and economic development. However, it remains unclear how much technological advances alone can mitigate climate change and the associated economic losses in the future. Through designing a suite of technological advances scenarios and using an earth system model with an integrated assessment model, we illustrate that rapid technological progress without production control might achieve the 2°C global warming target in the 2100s. Relative to a world of stagnant technology, the frequency (intensity) of extreme warm events at the end of the 21st century (2081–2100) would be reduced by ∼21% (5.5°C) via rapid technological advances, with a reduction in extreme precipitation (droughts) by ∼41% (10 times). Furthermore, fast technological advances may reduce the global economic losses linked with climate change at 2081–2100 by ∼21% and those in China related to floods (droughts) by 86% (67%). Our results highlight the potential of technological advances to fill the emission gap between the Paris Agreement and unconditional Nationally Determined Contributions and hence to efficiently mitigate global warming.

Climatic Warming and Humidification in the Arid Region of Northwest China: Multi-Scale Characteristics and Impacts on Ecological Vegetation - Qiang Zhang; Jinhu Yang; Wei Wang; Pengli Ma; Guoyang Lu; Xiaoyun Liu; Haipeng Yu; Feng Fang (Journal of Meteorological Research, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Correction to: Greater probability of extreme precipitation under 1.5 °C and 2 °C warming limits over East-Central Asia - Meng Zhang; Haipeng Yu; Andrew D. King; Yun Wei; Jianping Huang; Yu Ren (Climatic Change, 2020)

Greater probability of extreme precipitation under 1.5 °C and 2 °C warming limits over East-Central Asia - Meng Zhang; Haipeng Yu; Andrew D. King; Yun Wei; Jianping Huang; Yu Ren (Climatic Change, 2020)

Study of Top-down and Bottom-up Approaches by Using Design of Experiment (DoE) to Produce Meloxicam Nanocrystal Capsules - Tao Liu; Xinxin Yu; Haipeng Yin (AAPS PharmSciTech, 2020)

Multi‐model assessment of global temperature variability on different time scales - Haipeng Yu; Yun Wei; Qiang Zhang; Xiaoyue Liu; Jianping Huang; Taichen Feng; Meng Zhang (International Journal of Climatology, 2020)
This study explores the near‐surface air temperature (TAS) prediction skills at different time scales via coupled climate models that were involved in the Coupled Model Intercomparison Project phase 5 (CMIP5). The simulation skills of the global mean TAS are first assessed between the observations and models; then, the temporal variability is separated into three parts (the linear trend, decadal variability and inter‐annual variability), and each part is compared with the observations. It is found that the global mean TAS anomaly and the decadal variability are well captured by the model, while the inter‐annual variability is poorly presented. In all the three parts of different time scales, there are larger differences among the 18 models, and the ensemble mean of CMIP5 is the closest to the observations. Besides, the TAS decadal variability is better presented for global ocean than for global land. In the assessment of climate oscillation, it is found that the models can well reproduce the TAS decadal variation patterns correlated with the Pacific Decadal Oscillation (PDO) and the inter‐annual variation patterns correlated with El Niño–Southern Oscillation (ENSO) but poor for the decadal variation patterns related to the Atlantic Multidecadal Oscillation (AMO). This study provides a reference assessing the simulation skills of climate models and an indicator evaluating the advantage of CMIP6 in comparison with CMIP5.

The Influence of Rainfall on Landslide Stability of an Open-Pit Mine: The Case of Haizhou Open-Pit Mine - An Bo; Zhu Chun; Liu Kuiming; Li Sitong; Tao Zhigang; Li Haipeng; Yu Haoran (Geotechnical and Geological Engineering, 2019)

Drylands climate response to transient and stabilized 2 °C and 1.5 °C global warming targets - Yun Wei; Haipeng Yu; Jianping Huang; Tianjun Zhou; Meng Zhang; Yu Ren (Climate Dynamics, 2019)

Comparison of extreme temperature response to 0.5 °C additional warming between dry and humid regions over East–central Asia - Meng Zhang; Haipeng Yu; Jianping Huang; Yun Wei; Xiaoyue Liu; Tinghan Zhang (International Journal of Climatology, 2019)
The additional 0.5 °C warming from 1.5 to 2°C global target has a significant impact on the occurrence of extreme temperature events. While the arid and semi‐arid areas (ASA) and humid areas (HA) present different response characteristics to the additional global mean 0.5 °C warming due to their differences in thermal properties. In this study, both the stabilized and transient 1.5 °C (2 °C) global warming scenarios projected by the Community Earth System Model (CESM) are used to compare the extreme temperature responses between the ASA and HA to the 2 and 1.5 °C global warming targets over East–central Asia. The results indicate that cold fixed‐threshold indices (frost days [FD] and icing days [ID]) will decrease more rapidly in ASA, by approximately 10 days (1.5 °C) and 15 days (2 °C) compared to the historical period, respectively. Warm fixed‐threshold indices (summer days [SU] and tropical nights [TR]) will become more common in HA, especially southeast of China. Under 1.5 °C target, the increase of intensity indices is equal to the average temperature warming response (1.5 °C), while the additional 0.5 °C warming makes the response of intensity indices much greater than 0.5 °C. Under 0.5 °C warmer world, the daily temperature range (DTR) will experience a 0.5 °C increase in most HA and a 0.2–0.5 °C decrease in ASA during winter. As a whole, the additional 0.5 °C warming has an amplified effect and the 1.5 °C global warming target could reduce the extreme temperature events significantly over East–central Asia.

Genome-Wide Identification of Circular RNAs in Fungal Parasite Nosema ceranae - Rui Guo; Dafu Chen; Huazhi Chen; Cuiling Xiong; Yanzhen Zheng; Chunsheng Hou; Yu Du; Sihai Geng; Haipeng Wang; Zhou Dingding; Guo Yilong (Current Microbiology, 2018)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Comparison of the Pacific Decadal Oscillation in climate model simulations and observations - Yun Wei; Haipeng Yu; Jianping Huang; Yongli He; Bin Yang; Xiaodan Guan; Xiaoyue Liu (International Journal of Climatology, 2018)
The ability of climate models to simulate the Pacific Decadal Oscillation (PDO) and its global teleconnections is examined using the outputs of 20 Coupled Model Intercomparison Project (CMIP5) models from historical experiments. It is shown that the global warming trend is reproduced by the models, but there is a considerable difference between the models in the PDO region. The standard deviation of detrended sea surface temperature anomalies (SSTAs) in the models is similar to that of the observations, especially in the central and eastern equatorial Pacific and the North Pacific, which are the regions closely associated with the PDO and El Nino‐Southern Oscillation. The globally averaged SSTA during 1900–1940 in the CMIP5 models and observations showed large divergence, which is mainly due to the SSTA in the PDO region. The most significant cycle of the PDO indexes in most of the models had a 60–80 years period, which is different from the observed PDO period (40–60 years). However, the models perform better for the spatial pattern of the PDO, and 90% of the spatial correlations between the models and observations of the spatial pattern of the PDO are above 0.8. In addition, the models can simulate the basic correlation between the PDO and Pacific SSTA variability, but most of them overestimate the relationship in the Indian and Atlantic Oceans. The CMIP5 models are better at simulating the impact of the PDO on winter precipitation in southern North America but are less accurate in simulating summer precipitation in eastern China. This is probably because most of the models are not accurate in simulating the impacts of the PDO on the western Pacific subtropical high and the East Asian summer monsoon.

Targeting Suppressive Oligonucleotide to Lymph Nodes Inhibits Toll-like Receptor-9-Mediated Activation of Adaptive Immunity - Chunsong Yu; Myunggi An; Evan Jones; Haipeng Liu (Pharmaceutical Research, 2018)

Improved Oral Bioavailability and Liver Targeting of Sorafenib Solid Lipid Nanoparticles in Rats - Haipeng Wang; Huiyun Wang; Wenlong Yang; Mengjie Yu; Shuilin Sun; Baogang Xie (AAPS PharmSciTech, 2018)

Response of chironomid assemblages to East Asian summer monsoon precipitation variability in northern China since the last deglaciation - Haipeng Wang; Stephen J. Brooks; Jianhui Chen; Yu Hu; Zongli Wang; Jianbao Liu; Qinghai Xu; Fahu Chen (Journal of Quaternary Science, 2016)
We investigate chironomid assemblages in a sediment core from Gonghai Lake, which is located on the East Asian summer monsoon (EASM) boundary in northern China, to quantify EASM variability during the past 13.5 ka BP. Six significantly different chironomid assemblage zones indicate that maximum precipitation and water depth occurred in the mid‐Holocene (8270–2700 cal a BP) and the minimum period was the past 1250 years. A modern dataset of 44 lakes near Gonghai Lake was sampled to calibrate the response of chironomid assemblages to precipitation. Our results demonstrate that mean annual precipitation is the most significant environmental variable influencing modern chironomid assemblages in this monsoonal region. Maximum EASM precipitation in the mid‐Holocene, indicated by chironomid assemblages in the monsoon fringe, contrasts with the early Holocene EASM maximum suggested by stalagmite δ 18 O data from southern China, but is consistent with other evidence. Our findings are compatible with the proposal that the stalagmite δ 18 O variations in southern China may not reliably reflect the evolution of EASM since the last deglaciation.

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Experimental and analytical study on seismic behavior of steel-concrete multienergy dissipation composite shear walls - Hongying Dong; Wanlin Cao; Haipeng Wu; Qiyun Qiao; Chuanpeng Yu (Earthquake Engineering and Engineering Vibration, 2015)

Development of the analogue-dynamical method for error correction of numerical forecasts - Haipeng Yu; Jianping Huang; Weijing Li; Guolin Feng (Journal of Meteorological Research, 2014)

A chaotic analysis on air pollution index change over past 10 years in Lanzhou, northwest China - Bo Yu; Chengmin Huang; Zuhan Liu; Haipeng Wang; Lili Wang (Stochastic Environmental Research and Risk Assessment, 2011)

A knowledge-based method to predict the cooperative relationship between transcription factors - Lingyi Lu; Ziliang Qian; XiaoHe Shi; Haipeng Li; Yu-Dong Cai; Yixue Li (Molecular Diversity, 2010)

Protein sumoylation sites prediction based on two-stage feature selection - Lin Lu; Xiao-He Shi; Su-Jun Li; Zhi-Qun Xie; Yong-Li Feng; Wen-Cong Lu; Yi-Xue Li; Haipeng Li; Yu-Dong Cai (Molecular Diversity, 2010)